Moodle & Co. auf dem Weg zur Personal Learning Environment - Jörg Hafer; Alexander Kiy; Ulrike Lucke (FernUniversität Hagen, 2014)
Based on the typical IT infrastructure for e-learning in higher education and the contemporary research on Personal Learning Environments (PLEs) the paper shows how existing tools and services can be brought together to meet the needs of modern, technology enhanced classroom-based teaching. For this interdisciplinary development process both traditional software, development methods and existing PLE models offer only little guidance. The paper describes the approach and the interim results of a campus-wide project at the University of Potsdam. Therefore first typical teaching and communication scenarios are identified from which afterwards the requirements for a supporting platform are derived. This leads to a comprehensive collection of considerable services and functions, which have to be integrated according to their specific use in an educational technology system. Based on this fundamental approaches for integration and technical details of this mash up are considered in an overview of all relevant services and gets transferred into an integrated system architecture. The paper describes the exemplary realization using the Liferay portal technology in which the above-defined scenarios are implemented. Additional adjustments with regard to personalized and adaptive learning (and working) environments are supported too and described briefly